Diagnostic performance of intravoxel incoherent motion diffusion‐weighted imaging in the assessment of the dynamic status of myocardial perfusion. Issue 6 (7th May 2018) - An, Dong‐Aolei; Chen, Bing‐Hua; Rui‐Wu; Shi, Ruo‐Yang; Bu, Jun; Ge, Heng; Hu, Jiani; Xu, Jian‐Rong; Wu, Lian‐Ming
Abstract : Background: Acute myocardial infarction (AMI) is a major cause of morbidity and mortality worldwide and places a significant financial burden on our society. Purpose: To determine the feasibility of cardiac intravoxel incoherent motion (IVIM) in the consecutive evaluation of myocardial perfusion in myocardial infarction patients postpercutaneous coronary intervention (PCI) and to investigate the dynamic biological phenomena in myocardial perfusion after AMI. Study Type: Prospective observational study. Population: Twenty ST‐segment elevation myocardial infarction (STEMI) patients after reperfusion therapy and 12 healthy volunteers served as controls. Field Strength/Sequence: Cardiac MRI at 3T, including steady‐state free precession (SSFP) cine imaging, T2 ‐short time inversion recovery (T2 ‐STIR), late gadolinium enhancement (LGE), T2 mapping, and IVIM diffusion‐weighted imaging (DWI) were performed. Assessment: Myocardial T2 value and IVIM‐DWI‐associated parameters (ADCfast, ADCslow, and f value) of the infarcted myocardium at different timepoints, remote myocardium, and normal myocardium were analyzed by two experienced radiologists. Statistical Tests: Independent sample's t ‐test, Pearson's, and Spearman's correlation and interobserver variability were applied. P ≤ 0.05 was considered significant. Results: The T2 value in ischemic myocardium measured on day 3 (73.58 ± 4.37 msec) was greater than at any other timepoint (24 hours, day 7, day 30; 66.66 ± 4.71 msec, 68.36 ± 4.18 msec, 64.98 ± 5.39 msec, respectively, P < 0.001). ADCfast and f values were significantly lower in ischemic myocardium than in the remote myocardium as well. The f value in ischemic myocardium at day 3 (0.0989 ± 0.02) was lower than at any other timepoint (24 hours, 7 day, 30 day; 0.1203 ± 0.02, 0.1109 ± 0.02, 0.1213 ± 0.02, respectively, P < 0.001. Data Conclusion: This preliminary study demonstrated that a dynamic process exists in the status of myocardial edema and myocardial perfusion in MI patients after PCI. The findings suggest myocardial perfusion would be best evaluated between day 3 and day 7. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1602–1609